Vulnerability Factors in Children and Teenagers Victims of Sexual Violence - Bustamante Maita, Sherly Tania (2024)
Sexual violence is a multidimensional problem with an increasing incidence, its consequences generate short and long term havoc on the victim, as well as on society. According to the theory of vulnerability, there are individual factors that make a person more susceptible to suffering damage from environmental conditions. Minors are vulnerable to being victims of sexual violence due to their evolutionary stage and in addition there are other factors that act as catalysts for victimization, which are not always identified in a timely manner by legal assistants and operators. Under a qualitative approach and product of the review of scientific literature, as well as the «Brasília Rules on Access to Justice for People in Vulnerable Conditions», this article systematizes a series of vulnerability factors in cases of violence. sexual and the means necessary for its evaluation. The results differentiate nine types of vulnerability factors that can act as mediators of the impact of sexual violence in this age group. Likewise, it is recommended that the vulnerability assessment be carried out from an interdisciplinary and forensic approach, in order to obtain results that form part of the body of evidence within the criminal process.